The relationship between components of the dynamic strength index and the slope of the force-velocity profile in the loaded countermovement jump in resistance-trained males and females - Scheller, C.; Peeler, J.; Duhamel, T.; Cornish, S. (International Journal of Strength and Conditioning, 2023)
The purpose of this study was to evaluate the relationship between the dynamic strength index (DSI) and the lower-body Force-velocity (F-v) profile. Eighty-six (n = 58 females) resistance-trained individuals were recruited to perform both the DSI and F-v profile testing protocols to evaluate this relationship, as well as relationships between the components that comprise each test. Spearman correlations were calculated between DSI, F-v profile slope, countermovement jump (CMJ) peak force (PF), isometric mid-thigh pull (IMTP) PF, and CMJ peak velocity (PV) across a series of loading conditions from an unloaded CMJ to an additional 100% bodyweight (BW) CMJ condition. No significant correlations (rs = 0.01; p > 0.05) were found between the DSI value and the F-v profile slope. Significant correlations were found between the DSI and CMJ/IMTP PF (rs range = -0.63 to 0.22; p < 0.05) and between CMJ/IMTP PF and measures of CMJ PV (rs range = 0.45 to 0.73; p < 0.05) across the loading conditions. Results suggest that the DSI is not correlated to the F-v profile slope. Two different means of evaluating muscular force in athletes are not correlated; we suggest that athletes require specific evaluations for specific performance characteristics when assessing muscular force.